HUBUNGAN STATUS EKONOMI DAN DUKUNGAN SUAMI DENGAN KEJADIAN DEPRESI POSTPARTUM - Ratna Kusuma, Wulan; Achyar, Khamidah (Jurnal Kesehatan, 2024)
Background: The issues postpartum mothers face in Puskesmas II Kembaran's working area are a lack of support, particularly from their husbands, and economic conditions that may not adequately meet their needs. Objective: This study aimed to determine the correlation between economic status, husband's support, and the incidence of postpartum depression in the working area of Puskesmas II Kembaran. Method: This quantitative study employed a Cross-Sectional approach. The total sampling technique was obtained to select 52 postpartum mothers within two weeks of delivery in the working area of Puskesmas II Kembaran. Data were collected using questionnaires and analyzed bivariate through the Chi-Square test. Results: The univariate analysis results revealed that the average age of postpartum mothers was between 20 to 35 years (94.2%), with a High School education level (42.3%), and primarily primiparous mothers (53.8%). Most postpartum mothers obtained a low economic status on average (59.6%) and a high economic status on average (40.4%). About (59.6%) of postpartum mothers received their husband's support, while (40.4%) did not. The incidence of mild postpartum depression in Puskesmas II Kembaran was (51.9%), and (48.1%) of respondents did not experience postpartum depression. The bivariate analysis using the Chi-Square test indicated a correlation between economic status, husband's support, and the incidence of postpartum depression in the working area of Puskesmas II Kembaran, with a P-value of 0.000. Conclusion: There is a correlation between economic status, husband's support, and the incidence of postpartum depression in the working area of Puskesmas II Kembaran. Therefore, economic status and husband's support are crucial for postpartum mothers.